Investimento direto estrangeiro na África Subsaariana: um estudo sobre crescimento e dependência - Fernandes, André Galhardo (2015)
The objective of this study is to evaluate the structural changes to which sub-Saharan Africa has been subjected. Among its main points are the relationship between foreign direct investment, and how it changed the productive structure of the studied countries. With a sizeable real growth, sub-Saharan Africa has drawn the attention of investors and, as we shall see, the GDP growth was also accompanied by growth of FDI's. In order to address relevant issues in this study, from the 49 countries present in sub-Saharan Africa only ten were selected. However, the national aggregate output of these ten countries amount more than 80% of the GDP of the region in 2013, according to the World Bank. Therefore, it is indeed a small sample from the point of view of the number of countries covered, but it does not loose the economic dimension that Africa has. In recent studies, much is said about African growth. In fact, the growth in the 2000s stands out, even though it is often calculated on very small bases compared to the central and transitional countries. Therefore, this dissertation proposes to conduct an analysis of how the macroeconomic growth and FDI inflows have changed the African structure and thus answer questions about the role of Africa after this growth and how trade and financial relations with the center countries have occurred; that is, answer questions that do not arise when gross domestic product alone is analyzed